Fair Salaries and the Moral Costs of Corruption - Klaus Abbink (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
In a bribery experiment, we test the hypothesis that distributive fairness considerations make relatively well-paid public officials less corruptible. Corrupt decisions impose damages to workers whose wage is varied in two treatments. However, there is no apparent difference in behaviour.
Keywords: C91; D62; D72; D73; K42; 330; Corruption; reciprocity; fairness; public sector salaries